Modelagem termodinâmica da adsorção de gases: um estudo teórico- computacional sobre sistemas não-ideais - Arvelos, Sarah (2017)
Adsorption is considered a complex phenomenon since it involves species of very different chemical and physical nature. This complexity is reflected on the nature of the adsorbent (which can be considered a homogeneous or heterogeneous solid) , on the solid-fluid interactions and on the fluid-fluid interactions. Thus, the objective of this work is to evaluate the effect of these variables on the behavior of the adsorption of multicomponent gases. In order to reach the objective, tools of classical thermodynamics, statistics and molecular simulation were used. Initially a study of the effect of the adsorbates relative sizes regarding to some adsorbents was carried out aiming to evaluate azeotrope-like behavior on adsorption. In this step two multi-site occupancy models and two vacancy solution models were tested. The results indicate that the relative size of the molecules is the most important parameter in the description of adsorption azeotropism. The effect of the heterogeneity of the solid on the performance of the multi-site occupancy models was assessed using the patchwise theory in conjunction with the semi-Gaussian distribution. The inclusion of the heterogeneity was evaluated through the energy distribution of the sites and also in relation to the pore size distribution, in the case of zeolites. The study indicates that the inclusion of energy and/or structural heterogeneity is not the main variable in the description behavior of the adsorption of highly non-ideal mixtures. Considering that molecular simulation is a powerful tool in the elucidation of complex phenomena, computational simulation studies were performed using Monte Carlo (MC) method applied to the Grand Canonic Ensemble (GCMC). Special focus was given to zeolitic adsorbents considering the richness of structures and potentialities of the silicon/aluminum (Si/Al) ratio and the type of compensation cation used. We investigate systems involving the adsorption of pure components and mixtures such as carbon dioxide and nitrogen,propane-CO2 and ethylene-CO2 mixtures, which show a selectivity inversion as a function of the Si/Al ratio. In this step, it can be observed that the use of molecular simulation is a tool to generate additional adsorption data, especially in low and high pressure regions, favoring the estimation of parameters of classical and statistical models and consequently the prediction of multicomponent adsorption. In addition, it was also observed that for all-silica zeolites, simple force field models, without accounting the electrostatic forces for both zeolite and carbon dioxide and nitrogen, are effective in the adsorption description of these species. However, for zeolites with different Si/Al ratios, especially involving mixtures of dissimilar components (such as propane-CO2), it is necessary to include the electrostatic forces to describe azeotropic behavior.